The value of family visits as an implementation of maintaining human dignity: a sociological perspective - Teresia Noiman Derung (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2024)
Family visits are urgently needed at this time because violence in the family is rife and has even increased from time to time. Victims of violence are generally women and children. The cause of violence in the family is due to a shift in understanding regarding the image of God that exists in humans to become a